Development of Digital Flow Valve Applied to Aero-Engine Fuel Control and Research on Performance of Its Flow Characteristics - Yuesong Li (Machines)
Digital valves have strong anti-pollution ability and good linearity, so they are more suitable for aero-engine fuel control. However, for high-precision flow control, incremental digital valves require a high-precision, high-dynamic servomotor drive; binary-coded digital valves require many on/off valves; and high-speed switching digital valves can cause flow shock and pulsation. In this study, an aero-engine fuel control decimal-coded digital flow valve was developed, which not only has the advantages of digital valves but also avoids the above problems. Firstly, the structure and operation principle of the decimal-coded digital flow valve is introduced; then, its model is established based on Simulink/Simcape, and its flow characteristics are simulated and analyzed. Then, experiments on the flow characteristics are presented. The simulation and experiment show that under a supply pressure of 1 MPa, 2 MPa, and 3 MPa, the maximum flow of the decimal-coded digital valve is 11.4457 L/min, 16.3719 L/min, and 19.3733 L/min, and the control accuracy is 0.0775 L/min, 0.1086 L/min, and 0.1294 L/min, respectively. In addition, it has very good linearity, and the settling time is less than 0.09s.